Our media and our violent generations in the world: a psychological perspective / Ihshan Gumilar and Abdul Rasyid - Gumilar, Ihshan; Rasyid, Abdul (Centre for Media and Information Warfare Studies, 2008)
Media are reflections of our social life. Violence frequently appears in our media through various programs. Exposing too much of violence in the news and other programs will create a generation that is thirsty for violence and perceives it as common means to achieve their own goal. The media influence a way of thinking of young generations and automatically create the perception of violence as something which is acceptable, then, the actual behavior is correspondingly displayed. As youths generations, sooner or later they will hold a role in the society when they grow up later on. They will act (violent) accordingly in the society based on their own knowledge (pertaining to the violence) that has been shaped for many years through the media. When many youth generations produce violent behaviors society will turn into chaos. Consequently, the violent society will shape a violent world. Emphasizing too much on the importance of gained profits, from exposing violent programs especially, is not the only side that has to be given attention but the social problems that result is more important and demand much more cost than the obtained profits itself. Implementing some policies that confine the broadcast of too much violence is a way of improving the situation. It is further followed by emphasizing the role of religion and parents in the family setting, while cooperating with educational institutions is taken into consideration as well.